Rediscovery of Bombus rufipes Lepeletier 1835 (Hymenoptera: Apoidea: Bombidae) on Mount Slamet - Imam Widhiono; Trisno Haryanto; Eming Sudiana; Elly Proklamasiningsih; Edy Yani (Universitas Gadjah Mada, 2022)
Bombus rufipes Lepeletier 1835 (Hymenoptera: Bombidae) is the only species of Bombidae found in Java. Recent information suggests that it occurs in Java on Mounts Salak 1200 m asl., Mt. Halimun, Mt. Pangrango Gede Complexes, Mt.Cermai, (West Java) Mt.Slamet , Mt. Merapi, Mt. Merbabu, Mt Telomoyo (Central Java) and Mt Argopuro (East Java) , at altitudes above 1,500 m asl. We sought to rediscover this species on Mount Slamet by surveying natural forests at altitudes of 1,500–2,500 m asl on the eastern slopes of Mount Slamet, from August to October 2020 and August to October 2021. Descriptive and morphometric data were obtained and analyzed. The survey revealed five colonies nesting on the ground at an average depth of ca. 70 cm; the colonies contained 18–24 individuals and 22–36 cells (brood, honey, and pollen cells). Based on morphometric measurements and the description of Frison (1930), the species was identified as Bombus rufipes Lepeletier 1835. Therefore, Bombus rufipes still occurs on Mount Slamet. These results provide basic information that should aid further research on this species.